Consumer Buying Behaviour towards Life Insurance Policies in Western Odisha - Ambaris Pratap Singh,Dr. Chandra Bhooshan Singh, (Journal of Computational Analysis and Applications (JoCAAA), 2024)
In India the awareness regarding insurance is less as compared to other countries. If an Indianor international life insurance companies are seeking to serve Indian insurance market it seems more profitable